Optical tomography system based on charge-coupled device linear image sensors: Particle size measurement - Mariani, Idroas; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; M. N., Ibrahim (Elsevier B.V., 2011)
Description link to publisher's homepage at http://www.elsevier.com/